2019
DOI: 10.5821/sibb.27.1.9279
|View full text |Cite
|
Sign up to set email alerts
|

The role of versican in the skin ECM and its interaction with hyaluronic acid

Abstract: The extracellular matrix (ECM) is a structural network that comprises the bulk of the tissues. It acts as a supporting scaffold for the cells to develop their function and plays an active role in many processes such as proliferation and migration. Therefore, the ECM is an interesting object of study for regenerative medicine. In this article we make an extensive review of two key components of the ECM: the glycosaminoglycan Hyaluronic Acid (HA) and the proteoglycan Versican (Ver). These two molecules are prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Versican regulates the cell and tissue behaviors through interactions with various ECM proteins, such as collagen I, fibronectin, and fibulins 42 . In addition, versican interacts with HA to create a pericellular matrix that facilitates cell sorting, proliferation, migration, and survival 43 . In this study, we found that HPE significantly increased the expression of both versican (VCAN) www.nature.com/scientificreports/ and hyaluronan synthase 2 (HAS2) transcripts in NHDF cells.…”
Section: Discussionmentioning
confidence: 99%
“…Versican regulates the cell and tissue behaviors through interactions with various ECM proteins, such as collagen I, fibronectin, and fibulins 42 . In addition, versican interacts with HA to create a pericellular matrix that facilitates cell sorting, proliferation, migration, and survival 43 . In this study, we found that HPE significantly increased the expression of both versican (VCAN) www.nature.com/scientificreports/ and hyaluronan synthase 2 (HAS2) transcripts in NHDF cells.…”
Section: Discussionmentioning
confidence: 99%